2022
DOI: 10.1149/10701.9249ecst
|View full text |Cite
|
Sign up to set email alerts
|

Nutrigenomics in Lifestyle Disorders: A Review

Abstract: In the era of increasing unhealthy dietary and lifestyle habits, maintaining a healthy diet is really important to prevent a broad spectrum of diseases. Lifestyle diseases occur due to certain unhealthy daily habits (smoking, unhealthy diet, and physical inactivity) that lead to inappropriate relationships with the environment. The consumption of food in an improper quantity and lacking in quality can have adverse effects on an individual’s health. Diet can bring about certain changes in genes which can be stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 79 publications
(98 reference statements)
0
3
0
Order By: Relevance
“…The findings show that most professional officers have time to eat in the evening (85.1%). They tend to get more than those who snack before work in the morning (58.1%) [36].…”
Section: Eating Pattern Of Police Personnelmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings show that most professional officers have time to eat in the evening (85.1%). They tend to get more than those who snack before work in the morning (58.1%) [36].…”
Section: Eating Pattern Of Police Personnelmentioning
confidence: 99%
“…A crosssectional study conducted to assess police health issues in Viayawada reported 58 % being average, 35 % being overweight and 7 % being obese. It has also been recorded that 25 % of police personnel were anaemic in agreement, majority (72%) of police personnel in Bangladesh had normal nutritional status, 24% were overweight, 3% were obese, while underweight was negligible [36,37].…”
Section: Nutritional Status Of Police Personnelmentioning
confidence: 99%
“…Nevertheless, studies are scarcely comparable and reproducible not only because of the lack of standardized protocols, biological matrix or sample size but mainly because of the heterogeneous population and clinical variability included. Increasing evidence shows that disease-related intrinsic factors altogether with lifestyle factors may influence epigenetic mechanisms and identifying them is crucial to find unbiased reliable factors associated with a specific disease [27][28][29].…”
Section: Introductionmentioning
confidence: 99%